Characteristics of LGBTQ+ Patients and Their Care in Comparison with Heterosexual Individuals: What Is Important for the OBGYN? - Gabija Didžiokaitė; Paulina Leškevičiūtė; Aida Kuznecovaitė; Virginija Paliulytė (Medicina, 2025)
Background and Objectives: Women of the LGBTQ+ community, like heterosexual women, face a wide range of health issues and have a right to comprehensive healthcare. Unfortunately, they often do not seek healthcare due to concerns about possible discrimination or prejudice. The aims of this study were to analyze and compare experiences of LGBTQ+ individuals and heterosexual women during OBGYN appointments in Lithuania as well as to analyze the health of individuals whose biological gender is female and their lifestyle’s effect on their health. Materials and Methods: An anonymous online survey was conducted. Respondents answered questions regarding their gender and social identity; obstetrical, gynecological, and general clinical history; sexual life characteristics; and their experiences of visiting OBGYNs in Lithuania. Results: This study revealed that some lifestyle habits of LGBTQ+ respondents are more similar to those of heterosexuals than is often hypothesized. However, it also underscored such issues as the more common consumption of psychotropic substances, higher rates of depression, and more prevalent risky sexual practices among the LGBTQ+ community, as well as some neglected topics of OBGYN care in Lithuania. Conclusions: This study is the first in Lithuania to analyze the characteristics of LGBTQ+ individuals whose biological sex is female in relation to the field of obstetrics and gynecology. It provides important insights for the further improvement of the healthcare system regarding this topic.